Minilo je sedemdeset let od izida Jarčeve zbirke Človek in noč - Šurla, Andrej (Jezik in slovstvo, 1997)
Around the Easter of 1927, Miran Jarc published his collection of poems Man and the Night (Človek in noč). In it he collected the poems he wrote between 1917 and 1925. He had played with teh idea of publishing a colletion before, which is evident from several earlier manuscript collection. The main grid of Man and the Night with all the key poems had been produced in the late 1910s-early 1920s. The common denominator of Jarc's poems is a tendency towards documenting in poetry the maturation of his philosophical views, which was happening as a constant interwinnig of yearning and awareness of the relativity of knowledge. The external form has to reflect the internal charge of the content. Therefore the disharmonious modernity does not allow for any formal artism, especially not the fashionable sonnetism. The collection appeared at the time of critical Slovene polemic with expressionism and met with a lot of attention among literary critics.
Keywords: Jarc, Miran, 1900-1942; slovenska poezija; slovenski pesniki; biografije; Jarc, Miran: Človek in noč; literarne študije